Our friends, the enemy - Gwyther, Alex (Oberon modern plays., 2013)
"The Western front, Christmas 1914: lights appear from the German trenches, ghosts rise from behind the horizon, soldiers meet between the firing lines. The events which follow are some of the most astounding stories of the Great War told through the eyes of one soldier, Private James Boyce ... Our Friends, The Enemy is an acclaimed one-man show combining theatre and spoken word to capture the story of the Christmas truce from the First World War"--Page 4 of cover.